Creatine monohydrate ingestion-related placebo e effects on brief anaerobic exercise performance. A laboratory investigation - Szabo, A.; Szemerszky, R.; Dömötör, Z.; De la Vega, R.; Köteles, F. (Cuadernos de Psicología del Deporte, 2017)
People’s thoughts influence their action that led researchers to investigate the placebo effect in exercise performance. In the current study the placebo effects of creatine monohydrate on a one-minute anaerobic step-exercise performance were examined in a double blind laboratory inquiry. University students (n = 79, 64.5% women) were randomly assigned to one of three experimental conditions: 1) intervention (ingestion of 80 mg/kg dissolved creatine monohydrate, n = 26), 2) placebo (ingestion of dissolved corn starch, thought to be creatine, n = 26), and 3) no-intervention control (ingestion of drinking water only, n = 27). After a baseline measurement, participants have consumed their respective drinks and 40 minutes later the 1-minute exercise was repeated. While analysis of variance revealed no group level differences in actual and perceived change in performance, the latter was linked to participants’ expectations regarding performance on the second exercise test in the correlation analysis. Two thirds of the participants in the current study believed that their performance would improve in the actual test-exercise. However, these expectations were not linked to creatine ingestion. ese ndings suggest that (1) a single dose of creatine monohydrate does not affect anaerobic performance, (2) in low-challenge and low-subjective-importance “articial” research conditions suffcient expectations could not be evoked, and probably due to the lack of creatine-related expectations the placebo eects did not emerge.